The language of the eyes : science, sexuality, and female vision in English literature and culture, 1690-1927 - Ogden, Daryl, 1965- (SUNY series in feminist criticism and theory., 2005)
"While Darwinian and Freudian theories of vision and sexuality have represented women as lacking visual agency, Daryl Ogden's The Language of the Eyes argues that "the gaze" is not merely a masculine phenomenon, and that women have powerfully desiring eyes as well. Ogden offers a comprehensive cultural history of female visuality in England by analyzing scientific writings, conduct books, illustrated periodicals, poetry, painting, and novels, and he makes important and hitherto unrecognized connections between literary history, cultural studies, and science studies. In so doing, Ogden accomplishes what numerous feminist critics - especially film theorists - have not: the recovery of the modern female spectator from historical obscurity."--Jacket